Harmonising Perspectives: Understanding the Resident’s Voice and Care Homes’ Culture - Fenech, George; Marmara, Letizia (Magyar Gerontológia, 2024)
One must focus on the concept of dealing with an older person who is battling with the reality of having to leave the comfort zone for a good number of years to enter a different world within an institution. Working towards reaching new cultural aspirations can be disturbing in its own way. We all must educate ourselves about all the influences affecting this transformation.